Autonomy in Language Teaching and Learning (British Journal of Multidisciplinary and Advanced Studies, 2023)
The present study attempts to test the hypothesis of compromised learner autonomy hinders students’ ability to demonstrate critical thinking in oral communication activities in Japanese University EFL classes. Two surveys were administered to advanced-level L2 learners (N=168). The results showed a correlation between teacher dependence and the inability to demonstrate critical thinking skills in the majority of the students (N=168). Furthermore, twenty students, who represented the remaining minority, perceived themselves as independent/autonomous learners in the initial survey and identified as the ad hoc group. In the second survey, the ad hoc group checked all the affirmative statements of critical thinking skills. Despite being a small sample, the positive correlation between autonomous language learning experience and critical thinking warrants further investigation into the link between learner autonomy and critical thinking in English language education.